Revisionary notes of the genus Hypodoryctes Kokujev, 1900 (Hymenoptera, Braconidae: Doryctinae) from Vietnam, with descriptions of five new species - Oanh, Nguyen Thi; Long, Khuat Dang; Pham, Nhi Thi; Dzuong, Nguyen Van; Nghiep, Hoang Thi (Zootaxa, 2026)
Hypodoryctes Kokujev, a relatively small genus previously comprising ten species is revised. This paper includes descriptions and illustrations of five new species of Hypodoryctes from Vietnam, viz. Hypodoryctes albicyclus Long, sp. nov.; H. bicolor Long, sp. nov.; H. nebicolor Long, sp. nov.; H. netango Long, sp. nov.; and H. vietnamicus Long, sp. nov. A checklist and distribution of all known species of Hypodoryctes are provided. A key to Hypodoryctes species from the Eastern Palaearctic and Oriental regions is also given.